Optimizing the Use of Online Tacs Applications (Traffic Accident Claim System) in the Service of Traffic Accident Victims by the Ponorogo Police Traffic Unit - Hegar Gagah Anantaka (Advances in Police Science Research Journal, 2021)
The background of this research is the increasing number of traffic accidents in Ponorogo, so an innovation emerged that was implemented by the Ponorogo Police Traffic Unit together with hospitals and Jasa Raharja in April 2020 in the form of using the TACS Online Application to make it easier for people who were victims of traffic accidents to get services. from the police, hospitals, and Jasa Raharja quickly, as well as avoiding the complicated bureaucracy as has been arranged in a cooperation agreement / MoU. However, until January 2021, there are still many people who do not understand this service system, so it is considered not optimal. Therefore, a study was conducted that aims to determine the use of the TACS Online Application, the influencing factors, and the optimization of the use of the TACS Online Application. This research was conducted with a qualitative approach, using case study research methods, as well as data collection techniques by interviewing, observing, and reviewing documents. The results of the study found that the use of the TACS Online Application to date is for basic legal components, systems, mechanisms, and procedures, facilities, infrastructure/facilities, internal control, handling complaints, suggestions, and input, number of implementers, service guarantees, and performance evaluation of implementers. not meet the standards. The influencing factors, namely innovation, communication channels, and social systems are inhibiting factors. The optimizations that have been carried out include socializing the latest service system to the general public along with making a schedule of activity plans, making service knowledge videos, and making service promises and announcements. Based on the results of the study, the researchers suggest to carry out fixed budgeting, related to application maintenance, submitting Kominfo permits, submitting SOPs (Standard Operating Procedures) to the East Java Regional Police, making routine implementation reports accompanied by analysis and evaluation of leaders, maximizing socialization about services with the Dikyasa Unit, adding chat features, and expanding collaboration networks with other health units such as puskesmas.